2015
DOI: 10.5897/jaerd2013.0557
|View full text |Cite
|
Sign up to set email alerts
|

Role of local innovation in mechanisation of maize shelling: Evidence from Igabi, Chikun and Kajuru Local Government Areas, Kaduna State Nigeria

Abstract: The study assessed the benefits of a mechanical maize sheller made by a local artisan based on data from 90 farmers selected randomly and equally from Igabi, Chikun and Kajuru Local Government Areas of Kaduna State, Nigeria. Results of the study showed that 76.7% of the respondents adopted the maize sheller made by the local artisan as compared to 23.3% still engaged in hand-shelling of maize. Regarding performance of the maize sheller, 93.3% of the respondents indicated that they were very satisfied, while 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This may indicate that the region around Morogoro offers higher diversity in terms of agroecological conditions and cultivation, higher productivity on average, and better access to markets. Indeed, these factors have been identified as the most important barriers for adoption as pointed out by a study in Nigeria [12]. Therefore, when a household is located at the Morogoro region, these barriers are on average lower than in Dodoma, and therefore, our farm households located in the Morogoro region are more likely to adopt an UPS than those from the Dodoma region.…”
Section: Determinants Of Adoptionmentioning
confidence: 75%
See 3 more Smart Citations
“…This may indicate that the region around Morogoro offers higher diversity in terms of agroecological conditions and cultivation, higher productivity on average, and better access to markets. Indeed, these factors have been identified as the most important barriers for adoption as pointed out by a study in Nigeria [12]. Therefore, when a household is located at the Morogoro region, these barriers are on average lower than in Dodoma, and therefore, our farm households located in the Morogoro region are more likely to adopt an UPS than those from the Dodoma region.…”
Section: Determinants Of Adoptionmentioning
confidence: 75%
“…Farmers use the machine once per year after harvest. Both the maize-sheller and millet-thresher are capital intense and require five to six people to operate [12]. To receive access to one of the machines, the farmers had to group up and develop a financial plan.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These large stream-powered machines have now been mostly replaced with the use of the modern combine harvester that strips the kernels from the maize cob while the maize is being harvested in the field. In 2015, [7] assessed the level of adoption of mechanical maize shelling technologies are quite high, (76.7%) as compared to 23.3% who still engaged in hand shelling of maize. This suggested that a convergence of participatory innovation development framework is likely to be more beneficial to the farmers than the present technology -transfer approach to innovation development [8].…”
Section: Introductionmentioning
confidence: 99%